Outcome of Conservative Management in Biliary Ascariasis - A Study of 98 Cases - Khan, AS; Bhowmik, B; Hakim, HAN; Islam, MA (Journal of Dhaka Medical College, 2010)
Objectives: History of ascariasis is very old. One quarter of the world's population is known to be infected by ascariasis. It is endemic in various parts of Bangladesh. We aimed to study the various types of clinical presentations, complications and different diagnostic tools and to assess various options for the management of biliary ascariasis. Materials and Methods: Ninty eight cases of hepatobiliary ascariasis were studied over a period of 2 years (April 03 - April 05). All the patients were aged between 12 and 73 years and all were admitted with acute right upper abdominal pain. Ultrasound was the diagnostic tool of choice with 100% results. Results: In this study, biliary ascariasis was found to be more common in females 64.29% (64 patients). The most common presentation was upper abdominal pain in 100% of the patients (98 patients). Complications observed were obstructive jaundice in 08.16% (8 patients), cholangitis in 74.49% (73 patients). History of worm emesis was present in 21.42% (21 patients). Conservative management was successful in 96.94% (95 patients). During follow-up, worm reinvasion of the biliary system occurred in 7.1% (three patients). Conclusion: In endemic countries, biliary ascariasis should be suspected in patients with biliary disease. Most of the patients respond to conservative management. Keywords: Acute upper abdominal pain; biliary ascariasis; Ultrasonography DOI: 10.3329/jdmc.v19i1.6247 J Dhaka Med Coll. 2010; 19(1) : 25-28.